Estimation of alkaloid content of Ashwagandha (Withania somnifera) with HPLC methods - R. Elango, S. Rajasekar* and (Journal of Experimental Sciences, 2011)
Withania somnifera (Family; Solanaceae) is commonly known as Ashwagandha and is used in traditionally system of medicine since long time. Many compounds have been reported from the root part of the plant. In present study, comparative evaluation of microbial consortium and uninoculated control plant root collected from different geographically sources was done by HPLC. Methanol soluble root extract of the plant was subjected to Column chromatography to isolate and purify the phyto-constituents which can be termed as markers. Three compounds were isolated and purified. Compounds were characterized as withanone and withaferin-A. The third compound was found to be impure. Novel HPLC methods were developed for assessment of purity, for standardization and for estimation of the compounds. Simplicity of isolation and HPLC analysis for the compounds suggests that the compounds may be termed as markers for the standardization of the methanol extracts and preparations containing Withania somnifera.